Do Engineered Nanomaterials Affect Immune Responses by Interacting With Gut Microbiota? - Tang, Mingxing; Li, Shuo; Wei, Lan; Hou, Zhaohua; Qu, Jing; Li, Liang (Frontiers in Immunology, 2021)
Engineered nanomaterials (ENMs) have been widely exploited in several industrial domains as well as our daily life, raising concern over their potential adverse effects. While in general ENMs do not seem to have detrimental effects on immunity or induce severe inflammation, their indirect effects on immunity are less known. In particular, since the gut microbiota has been tightly associated with human health and immunity, it is possible that ingested ENMs could affect intestinal immunity indirectly by modulating the microbial community composition and functions. In this perspective, we provide a few pieces of evidence and discuss a possible link connecting ENM exposure, gut microbiota and host immune response. Some experimental works suggest that excessive exposure to ENMs could reshape the gut microbiota, thereby modulating the epithelium integrity and the inflammatory state in the intestine. Within such microenvironment, numerous microbiota-derived components, including but not limited to SCFAs and LPS, may serve as important effectors responsible of the ENM effect on intestinal immunity. Therefore, the gut microbiota is implicated as a crucial regulator of the intestinal immunity upon ENM exposure. This calls for including gut microbiota analysis within future work to assess ENM biocompatibility and immunosafety. This also calls for refinement of future studies that should be designed more elaborately and realistically to mimic the human exposure situation.